HUBUNGAN STATUS GIZI TERHADAP HIPERTENSI PADA LANSIA DI PUSKESMAS KAMPUNG DALAM PONTIANAK - Barabas, M Berly (ProNers, 2023)
ABSTRACT  Background: Hypertension, known as "the silent killer", has varied symptoms and almost the same symptoms as other medical conditions. Hypertension is caused by various factors, one of them is nutritional status. Objective: This research aims to determine whether there is a relationship between elderly nutritional status and hypertension in Community Health Center of Kampung Dalam Pontianak. Method: This is a quantitative research with observational analytic and observational cross-section design. The total sample of this research is 135 samples selected with consecutive sampling technique. The instruments of this research are BMI questionnaire and measurement tools which are mercury sphygmomanometer and weigh scale. Result: Hypothesis testing using Gamma test shows that there is no significant difference (p = 0,807). Conclusion: There is no relationship between the elderly nutritional status and hypertension in Community Health Center of Kampung Dalam Pontianak. Further research is needed to see factors that affect hypertension on elderly in Health Community of Kampung Dalam Pontianak .Key Word                             : Nutritional Status, Hypertension, elderly, Community Health Center.